Teaching Cross-Cultural and Comparative Perspectives of Teacher Development Online: A Reflective Practitioner Inquiry - Toukan, Elena; Niyozov, Sarfaroz (Comparative and International Education / Éducation comparée et internationale, 2023)
In this reflective practitioner inquiry, a course instructor and a graduate teaching intern examine the experience of teaching a graduate-level course about cross-cultural perspectives of teacher development. We inquire along three dimensions: assisting doctoral students to become effective and reflective university instructors; responding to course students’ questions and concerns about developing a meaningful academic community in an online learning environment; and conceptual issues of teaching comparative, international, and development education (CIDE) in university settings. Our key argument is that in order to succeed in the above three dimensions, professional reflexivity in CIDE higher education courses can be both conceptually and pedagogically multidirectional, by which experienced and novice instructors learn from each other as much as they learn from their students in an engaging and enriching online environment.